2019
DOI: 10.1002/masy.201800157
|View full text |Cite
|
Sign up to set email alerts
|

What Can Be Learned from the Polymerization of a Pyridine‐Based Two‐Component System

Abstract: Stable poly (4‐vinyl pyridine)/pyridine gels prepared by dissolving solid polymer in pyridine (the equimolar ratio of the pyridine moieties to the pyridine solvent molecules) exhibit sensor properties rapidly and reversibly increasing their conductivity upon irradiation by light in the UV‐Vis and NIR ranges. Both ionic and electronic mechanisms of conductivity were detected. The gels behave as polyelectrolytes involving the positively charged pyridine moieties and negatively charged saturated chains held toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…No more changes in absorption were observed after prolonged storage in the dark. The fluorescence spectrum of a thin layer of the gel sample irradiated for 6 h shown in the inset of Figure 1 covers the whole visible range and resembles the fluorescence spectrum of the irradiated pyridine samples [12]. The intensity of several peaks and shoulders observed in the fluorescence spectrum of irradiated pyridine depend on the excitation wavelength, and each of them belongs to a different soluble oligomer chain length (Supplementary Materials, Figure S2).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…No more changes in absorption were observed after prolonged storage in the dark. The fluorescence spectrum of a thin layer of the gel sample irradiated for 6 h shown in the inset of Figure 1 covers the whole visible range and resembles the fluorescence spectrum of the irradiated pyridine samples [12]. The intensity of several peaks and shoulders observed in the fluorescence spectrum of irradiated pyridine depend on the excitation wavelength, and each of them belongs to a different soluble oligomer chain length (Supplementary Materials, Figure S2).…”
Section: Resultsmentioning
confidence: 82%
“…Recently, we suggested that the appearance of the multi-band emission spectrum of pyridine, irradiated at 254 or 312 nm, cannot be explained by the formation of 5-amino-2,4-pentadienal alone and suggested that this aminoaldehyde undergoes oligomerization [12]. Gaining deeper insight into the photochemical processes within pyridine and its derivatives is important, in particular, since polyvinyl pyridines are known to exhibit potential for several industrial applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation